2022
DOI: 10.3389/fcell.2022.1018161
|View full text |Cite
|
Sign up to set email alerts
|

Increased Aurora B expression reduces substrate phosphorylation and induces chromosomal instability

Abstract: Increased Aurora B protein expression, which is common in cancers, is expected to increase Aurora B kinase activity, yielding elevated phosphorylation of Aurora B substrates. In contrast, here we show that elevated expression of Aurora B reduces phosphorylation of six different Aurora B substrates across three species and causes defects consistent with Aurora B inhibition. Complexes of Aurora B and its binding partner INCENP autophosphorylate in trans to achieve full Aurora B activation. Increased expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…This knowledge will be necessary to understand how a midzone Aurora B activity gradient mediates anaphase error correction and to test whether similar mechanisms operate during meiosis. Moreover, because Aurora B is overexpressed in highly aneuploid cancers ( Pfister et al, 2018 ; Smith et al, 2005 ; Takeshita et al, 2013 ) and its overexpression was recently shown to inhibit Aurora B activity toward different kinetochore substrates ( Britigan et al, 2022 ), it will be important to investigate whether anaphase surveillance and error correction mechanisms are disrupted in human cancers.…”
Section: Mechanism Of Anaphase Error Correctionmentioning
confidence: 99%
“…This knowledge will be necessary to understand how a midzone Aurora B activity gradient mediates anaphase error correction and to test whether similar mechanisms operate during meiosis. Moreover, because Aurora B is overexpressed in highly aneuploid cancers ( Pfister et al, 2018 ; Smith et al, 2005 ; Takeshita et al, 2013 ) and its overexpression was recently shown to inhibit Aurora B activity toward different kinetochore substrates ( Britigan et al, 2022 ), it will be important to investigate whether anaphase surveillance and error correction mechanisms are disrupted in human cancers.…”
Section: Mechanism Of Anaphase Error Correctionmentioning
confidence: 99%